2020
DOI: 10.3389/fcell.2019.00384
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Membrane and Vesicular Traffic in Regulation of the Hippo Pathway

Abstract: The Hippo pathway is a well conserved signaling cascade that modulates cell proliferation and survival in response to external cues such as cell:cell contact, injury, and nutritional status. Models of the Hippo pathway have evolved from a series of genetic interactions defined in the fruit fly Drosophila melanogaster into a complex series of biochemical mechanisms in which transmembrane and cytoskeletal proteins modulate cytoplasmic phosphatase and kinase activities that converge on the serine/threonine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…ARRDC3 suppresses GPCR-stimulated Hippo signaling by sequestering TAZ in the cytoplasm, thereby preventing gene induction, migration and metastasis of TNBC A previous study in Drosophila reported that Leash, a homolog of ARRDC3, interacts with Yorkie, the homolog of YAP and TAZ, and inhibits Hippo signaling by facilitating Yorkie degradation (Kwon et al, 2013;Verghese and Moberg, 2020). This discovery gave credence to the idea that mammalian ARRDC3 might regulate Hippo signaling through interactions with YAP and TAZ.…”
Section: Discussionmentioning
confidence: 85%
“…ARRDC3 suppresses GPCR-stimulated Hippo signaling by sequestering TAZ in the cytoplasm, thereby preventing gene induction, migration and metastasis of TNBC A previous study in Drosophila reported that Leash, a homolog of ARRDC3, interacts with Yorkie, the homolog of YAP and TAZ, and inhibits Hippo signaling by facilitating Yorkie degradation (Kwon et al, 2013;Verghese and Moberg, 2020). This discovery gave credence to the idea that mammalian ARRDC3 might regulate Hippo signaling through interactions with YAP and TAZ.…”
Section: Discussionmentioning
confidence: 85%
“…It is worth mentioning that previous studies have suggested critical roles of intracellular vesicular trafficking in activating Hippo signaling at the plasma membrane (Verghese & Moberg, 2019). Studies in mice also indicated a critical role of Rab11 in suppressing Yap activity by maintaining LATS kinase activity and YAP localization at adherens junctions (D'Agostino et al , 2019; Goswami et al , 2021).…”
Section: Discussionmentioning
confidence: 96%
“…YAP1 is the main effector downstream of the Hippo signaling pathway. It is a multifunctional intracellular connexin and transcription coactivator, which can have effects on many aspects of human development, growth, DNA repair, and endogenous homeostasis [ 51 , 52 ]. The abnormal expression of YAP1 is associated with the proliferation and invasion of various tumor cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%